Effectiveness of a Digital Pocketbook in Improving Knowledge of Long-Acting Contraceptive Methods among Women of Reproductive Age - Anjar Diasti Amalia Amna; Bima Suryantara; Fatya Nurul Hanifa (Indonesian Journal Publisher, 2026)
Background: Limited understanding among women of reproductive age regarding Long-Acting Reversible Contraceptive (LARC) methods, particularly implants and intrauterine devices (IUDs), remains a major barrier to the success of family planning programs. Objective: This study aimed to improve the knowledge of women of reproductive age regarding long-acting contraceptive methods, especially implants and IUDs, through digital pocket book-based education. Methods: This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design involving 15 women of reproductive age at Mutiara Hati Clinic. The intervention was conducted through participatory educational counseling using an Android-based digital pocket book, beginning with a pre-test, followed by material delivery, interactive discussion, and ending with a post-test. Data analysis using the Shapiro-Wilk test indicated that pre-test data were normally distributed (p = 0.600), while post-test data were not normally distributed (p = 0.002); therefore, the Wilcoxon Signed Ranks Test was applied. Results: The results showed that all respondents (100%) experienced an increase in post-test scores compared to pre-test scores, with a Z value of -3.450 and a significance level of p < 0.001. Participants’ knowledge levels improved from predominantly moderate and low categories at baseline to entirely good after the intervention. Conclusion: The findings show that digital pocket books are effective educational media for increasing knowledge of women of reproductive age regarding implant and IUD long-acting contraceptive methods.